2016
DOI: 10.1007/s13224-016-0901-3
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Maternal “Near-Miss” Events in a Tertiary Care Hospital of Central Gujarat, India

Abstract: Background Constant decline in maternal mortality ratio has given rise to the need of a new indicator. This search has motivated investigation of severe maternal morbidity-''maternal near-miss'' (MNM) event. World Health Organization (WHO) defines MNM as ''a woman who, being close to death, survives a complication that occurred during pregnancy, delivery or up to 42 days after the end of her pregnancy''. Methodology A hospital-based cross-sectional study was carried out at Sir Sayajirao General Hospital (SSGH)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 8 publications
3
16
1
3
Order By: Relevance
“…This study revealed the incidence of near-miss to be 30.1/1,000 obstetric admissions and 31.4/1,000 live births which is comparably higher than the regional literature. In recent Indian studies, near-miss rate was 20.6/1,000 obstetric admissions [4] and 17.8/1,000 live births [2]. The ratio of maternal near-miss to mortality was reported to be 5.6:1 and 2.6:1 [2,4], as compared to 3.8:1 in this study.…”
Section: Discussionmentioning
confidence: 40%
See 1 more Smart Citation
“…This study revealed the incidence of near-miss to be 30.1/1,000 obstetric admissions and 31.4/1,000 live births which is comparably higher than the regional literature. In recent Indian studies, near-miss rate was 20.6/1,000 obstetric admissions [4] and 17.8/1,000 live births [2]. The ratio of maternal near-miss to mortality was reported to be 5.6:1 and 2.6:1 [2,4], as compared to 3.8:1 in this study.…”
Section: Discussionmentioning
confidence: 40%
“…In recent Indian studies, near-miss rate was 20.6/1,000 obstetric admissions [4] and 17.8/1,000 live births [2]. The ratio of maternal near-miss to mortality was reported to be 5.6:1 and 2.6:1 [2,4], as compared to 3.8:1 in this study. In an Ethiopian study, it has been reported to be 8.01/1,000 live births [5].…”
Section: Discussionmentioning
confidence: 40%
“…Both MNMR and SMOR give an estimate of the amount of care and resources that would be needed to improve obstetric care in that area or facility. We reviewed studies done in different parts of India, and the near-miss ratio ranged from 120 to 10.4 ( Table 12) [10][11][12][13][14][15][16][17][18][19][20][21][22]. However, all these studies have used different criteria in identifying near-miss cases and hence technically not ideal for comparison.…”
Section: Discussionmentioning
confidence: 99%
“…2 The maternal mortality of India is presently 130/100,000 live births, although showing a large regional variation. 3 It is 300/lakh live births for Assam and 67/lakh live births in Kerala.…”
Section: Introductionmentioning
confidence: 99%